2016
DOI: 10.1097/mop.0000000000000375
|View full text |Cite
|
Sign up to set email alerts
|

Understanding autoimmunity of vitiligo and alopecia areata

Abstract: Purpose of review Vitiligo and alopecia areata are common, disfiguring skin diseases. Treatment options are limited and include non-targeted approaches such as corticosteroids, topical calcineurin inhibitors, narrow band UVB phototherapy, and other immune-modifying agents. The purpose of this article is to review shared, novel mechanisms between vitiligo and alopecia areata, as well as discuss how they inform the development of future targeted treatments. Recent findings Vitiligo and alopecia areata are both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 46 publications
2
68
0
10
Order By: Relevance
“…Cytokines secreted within the skin act as an early signal to help these autoreactive T cells locate stressed melanocytes. This is probably important because the epidermis is not vascularized, and so active mechanisms are required to help them efficiently locate melanocytes (33). Chemokines are small, secreted proteins that act as chemoattractants to guide T cell migration.…”
Section: Vitiligo Pathogenesismentioning
confidence: 99%
“…Cytokines secreted within the skin act as an early signal to help these autoreactive T cells locate stressed melanocytes. This is probably important because the epidermis is not vascularized, and so active mechanisms are required to help them efficiently locate melanocytes (33). Chemokines are small, secreted proteins that act as chemoattractants to guide T cell migration.…”
Section: Vitiligo Pathogenesismentioning
confidence: 99%
“…Various factors are involved in the pathogenesis of vitiligo including genetics, environment, oxidative stress as well as innate and acquired immunity . Oxidative stress triggers chemokines production from keratinocytes causing infiltration of melanocyte antigen‐specific CD8 + T cells into the epidermis, which have an adverse effect on the morphology of melanocytes and also induce their apoptosis by direct killing and IFN‐γ secretion . Several regulatory mechanisms including the concentration of indoleamine 2, 3‐dioxygenase, expression of programmed cell death protein ligand‐1 (PD‐L1) and cytotoxic T lymphocyte‐associated protein‐4 (CTLA‐4) by melanocytes, and also presence of Foxp3 + regulatory T cells have been introduced for peripheral tolerance induction and inhibition of autoimmune responses in the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Although the etiopathogenesis of AA has not been completely established yet, an autoimmune nature of the disease has been suspected with genetic predisposition . The hair follicle is an inherently immune‐privileged site with low expression levels of major histocompatibility complex . It is assumed that AA results from a breakdown in immune privilege and subsequent assault on the follicle by CD8 + T lymphocytes .…”
Section: Introductionmentioning
confidence: 99%
“…5 The hair follicle is an inherently immune-privileged site with low expression levels of major histocompatibility complex. 6 It is assumed that AA results from a breakdown in immune privilege and subsequent assault on the follicle by CD8 + T lymphocytes. 7 A recent study conclusively revealed a key role of a specific cytotoxic T-cell subset, NKG2D + CD + cytotoxic T cells, in the infiltration and destruction of the upper part of the hair bulb, without harming regenerative stem cells.…”
Section: Introductionmentioning
confidence: 99%